New Trends Affecting the Energy Policy in Global Level, Country Level and Company Level (Eurasian Journal of Engineering and Technology, 2023)
Recent events like the Russian-Ukrainian war and the corona pandemic have caused some changes in the energy industry. Despite being the primary source of energy in the world, fossil fuels have an adverse effect on the environment as a result of their large GHG emissions and air pollution. As a result, in order to create energy with the best efficiency and the least amount of environmental harm, the transition to renewable energy should be accelerated with the appropriate innovation. In this thesis, the impacts of energy generated from renewable sources are investigated from a global, national, and corporate standpoint. To accomplish the goals of the thesis, the author uses a questionnaire. Approximately 71 people took part in this survey. The findings indicate that the energy industry's adoption of renewable energy sources was stated to lessen pressure on energy prices, improve the capability of the world's energy to treat with the unavoidable effects of climate change, and lower costs related to pollution produced by fossil fuels. Additionally, it is said that utilizing renewable energy gives organizations a competitive advantage in the market. Because renewable energy provides a quick return on investment (ROI), can reduce energy prices, and can draw in new customers, it can also help businesses indirectly enhance productivity and income.